New InhA Inhibitors Based on Expanded Triclosan and Di-Triclosan Analogues to Develop a New Treatment for Tuberculosis - Sarentha Chetty; Tom Armstrong; Shalu Sharma Kharkwal; William C. Drewe; Cristina I. De Matteis; Dimitrios Evangelopoulos; Sanjib Bhakta; Neil R. Thomas (MDPI AG, 2021)
The emergence of multidrug-resistant (MDR) and extensively drug-resistant (XDR) tuberculosis (TB) has reinforced the need for the development of new anti-TB drugs. The first line drug isoniazid inhibits InhA. This is a prodrug requiring activation by the enzyme KatG. Mutations in KatG have largely contributed to clinical isoniazid resistance. We aimed to design new 'direct' InhA inhibitors that obviate the need for activation by KatG, circumventing pre-existing resistance. In silico molecular modelling was used as part of a rational structure-based drug-design approach involving inspection of protein crystal structures of InhA:inhibitor complexes, including the broad spectrum antibiotic triclosan (TCS). One crystal structure exhibited the unusual presence of two triclosan molecules within the Mycobacterium tuberculosis InhA binding site. This became the basis of a strategy for the synthesis of novel inhibitors. A series of new, flexible ligands were designed and synthesised, expanding on the triclosan structure. Low Minimum Inhibitory Concentrations (MICs) were obtained for benzylphenyl compounds (12, 43 and 44) and di-triclosan derivative (39), against Mycobacterium bovis BCG although these may also be inhibiting other enzymes. The ether linked di-triclosan derivative (38) displayed excellent in vitro isolated enzyme inhibition results comparable with triclosan, but at a higher MIC (125 µg mL−1). These compounds offer good opportunities as leads for further optimisation.